2022
DOI: 10.1101/2022.09.03.506461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of the alpha rhythm is linked to visual white matter pathways and visual detection performance

Abstract: Alpha is the strongest electrophysiological rhythm in awake humans at rest. Despite its predominance in the EEG signal, strong variations can be observed in alpha properties during development, with an increase of alpha frequency over childhood and adulthood. Here we tested the hypothesis that these changes of alpha rhythm are related to the maturation of visual white matter pathways. We capitalized on a large dMRI-EEG dataset (dMRI n=2,747, EEG n=2,561) of children and adolescents (age range: 5-21 years old) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Another line of studies also assessed the correlation between OR tissue properties and behavioral and functional measurements related to visual functions, such as eye dominance 183 and oscillations. 184 , 185 Webb and colleagues (2022) 186 reported that age-related differences in tissue properties of the OR can predict visual performance, suggesting that the tractometry approach is also useful in considering how aging on the white matter is related to visual functions.…”
Section: Tractometry Of Early Visual White Matter Tractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another line of studies also assessed the correlation between OR tissue properties and behavioral and functional measurements related to visual functions, such as eye dominance 183 and oscillations. 184 , 185 Webb and colleagues (2022) 186 reported that age-related differences in tissue properties of the OR can predict visual performance, suggesting that the tractometry approach is also useful in considering how aging on the white matter is related to visual functions.…”
Section: Tractometry Of Early Visual White Matter Tractsmentioning
confidence: 99%
“…One newly proposed solution to this challenge is to model the full shape of the tract profile using generalized additive models 264 (for a recent application of this approach in measurements from the optic radiation see 185 ). Other similar approaches use linear mixed effects models where each streamline is considered as a within-subject random factor 67 or use correction approaches analogous to those used in fMRI.…”
Section: Future Perspectives and Open Questionsmentioning
confidence: 99%